The microstratigraphy and depositional environments of Lida Ajer and Ngalau Gupin, two fossil-bearing tropical limestone caves of west Sumatra - Holly E. Anderson; Mike W. Morley; Conor McAdams; Jahdi Zaim; Yan Rizal; Aswan; Mika R. Puspaningrum; Agus T. Hascaryo; Gilbert J. Price; Julien Louys (Scientific Reports, 2024)
Abstract Lida Ajer and Ngalau Gupin are karstic caves situated in the Padang Highlands, western Sumatra, Indonesia. Lida Ajer is best known for yielding fossil evidence that places the arrival of Homo sapiens in Southeast Asia during Marine Isotope Stage 4, one of the earliest records for the region. Ngalau Gupin recently produced the first record of hippopotamid Hexaprotodon on the island, representing the only globally extinct taxon in Pleistocene deposits from Sumatra. Microstratigraphic (micromorphological) analyses were applied to unconsolidated fossil-bearing cave sediments from these two sites. We use micromorphology as part of a micro-contextualised taphonomic approach to identify the diagenetic processes affecting fossils and sediments within these caves, through phases of their depositional history. The fossil-bearing sediments in Lida Ajer have been subjected to a suite of natural sedimentation processes ranging from water action to carnivore occupation, which would indicate the fossils underwent significant reworking prior to lithification of the deposit. The results demonstrate that the base of the unconsolidated fossil-bearing sediments in Ngalau Gupin were derived from the interior of the cave, where the matrix was partially phosphatized as a result of guano-driven diagenesis. These observations can be used to test hypotheses about the integrity of incorporated vertebrate remains and to aid in local palaeoenvironmental reconstructions. The methods employed in this research have not previously been applied to cave sediments from sites in the Padang Highlands and provide key new insights into the palaeontological and natural history of the western region of Sumatra.